Anterior inferior iliac spine fracture: another component of selt belt syndrome? - Hussin, Paisal; Ramalingam, Kuharajan; Mawardi, Maliza; Che Hamzah, Fahrudin; Abdul Rashid, Ahmad Hisham (Ministry of Health, Brunei Darussalam, 2013)
Seat belt syndrome occurs when seat belts are used improperly, and it is a cause of significant morbidity and mortality. The spectrum of seat belt syndrome includes spinal, intra-abdominal and vascular injury. Here, we report the case of anterior inferior iliac spine avulsion fracture in association with seat belt injuries in a 24-year old man involved in a head on motor vehicle collision.